PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN DENGAN JOB RELEVANT INFORMATION SEBAGAI VARIABEL INTERVENING (STUDI EMPIRIS PADA PT. ALBASIA BHUMIPHALA PERSADA TEMANGGUNG) - Susi Sih Kusumawardhany (Prima Center Indonesia, 2018)
Recently a company faced by a very rapid changing and competitive environment. In order to win the competition, a company must increase their performance. Business globalization evoke continuously changing in all business aspect so an alteration became a normal condition. On of the management tool that often used by the management to manage their company is budget. Budget can be used by management as tool to plan and control the company activity. The purpose of the research is to examine the relationship between participative budget with job satisfaction and employee’s performanceand also the role of Job Relevant Information (JRI) as the intervening variable between participative budget with job satisfaction and employee’s performance. Variable that is used this research is participant budget, job satisfaction, employee’s performance and job relevant information (JRI). This research using survey method in which the researcher distribute questionnaire which include list of question to chosen respondents. Data analyses that were used in this research are validity and realibility test, Structural Equation Model and path analysis. The result shows that relationship between participative budget and job satisfaction figure out that participation in budgetary has positie in direct effect on employee’s job satisfaction and relationship between participative budget and job performance figure out that participation in budgetary has positive in direct effect on employee’s job performance. In addition, the relationship between participative budgetary and job satisfaction through job relevant information as an intervening variable shows that there is a significantly positive direct effect., while the relationship between participative budgetary a job performance through job relevant information as an intervening variable shows that there is a significantly positive direct effect.Keywords: participative budgetary, job satisfaction, job performance and job relevant information.